Becoming a mother of a second child: a scoping review - Guarda da Venda Rodrigues, Joana Rita (2018)
Background: Becoming the mother of a second child represents a singular and transformational period that demands a transition to new roles with repercussions in health and quality of life. However, the evidence portraying this transition in the current literature is scarce and sparse. Objective: mapping and describing the women’s experience in becoming the mother of a second child. Review method: a scoping review was conducted using the Joanna Briggs Institute methodology. Results: nine studies published between 1997 and 2013 have been identified, the participants and the time of data collection differ; none of which were carried out in Portugal. In one study women characterize this transition as a quest for a new balance and the remaining are related to gender and conjugality issues. Conclusion: the nine studies considered in the review were published over a period of 16 years, presenting some elements that characterize this transition. Further studies should be carried out to understand woman’s perspectives in depth when they become mothers for the second time.